2002
DOI: 10.1161/01.cir.0000016360.97819.44
|View full text |Cite
|
Sign up to set email alerts
|

Exercise-Induced Coronary Artery Vasodilation Is Not Impaired by Stent Placement

Abstract: Background-Stenting has proved beneficial for treating threatened closure and reducing restenosis after balloon angioplasty. However, the implantation of a coronary metallic prosthesis has been related to impaired vasomotion distal to the stent as assessed by acetylcholine infusion. Thus, the purpose of the present study was to determine the vasomotion of stented coronary arteries and to assess its influence on the vasomotion of adjacent vessel segments during bicycle exercise. Methods and Results-Biplane quan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
1
2

Year Published

2004
2004
2015
2015

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 28 publications
(34 reference statements)
2
30
1
2
Order By: Relevance
“…Gage et al 21 and Gordon et al 25 have shown vasoconstriction of stenotic but vasodilation of normal coronary vessel segments in response to exercise. Recently, we reported that stent implantation does not impair exercise-induced coronary artery vasodilation proximal and distal to the stented vessel, 17 as it was reported by Caramori et al 26 Sabate et al 19 have reported preserved endothelium-dependent vasodilation 6 months after brachytherapy, assessed by the vasomotor response to acetylcholine infusion. The contrary findings may be related to (1) the different techniques for measuring coronary vasomotor response (ie, pharmacological assessment of endothelial function by acetylcholine infusion versus flow-mediated changes induced by bicycle exercise) and (2) the different radiation dose (our brachytherapy group received 20 Gy, the brachytherapy group studied by Sabate et al, 19 14 Gy).…”
Section: Limitationssupporting
confidence: 65%
See 2 more Smart Citations
“…Gage et al 21 and Gordon et al 25 have shown vasoconstriction of stenotic but vasodilation of normal coronary vessel segments in response to exercise. Recently, we reported that stent implantation does not impair exercise-induced coronary artery vasodilation proximal and distal to the stented vessel, 17 as it was reported by Caramori et al 26 Sabate et al 19 have reported preserved endothelium-dependent vasodilation 6 months after brachytherapy, assessed by the vasomotor response to acetylcholine infusion. The contrary findings may be related to (1) the different techniques for measuring coronary vasomotor response (ie, pharmacological assessment of endothelial function by acetylcholine infusion versus flow-mediated changes induced by bicycle exercise) and (2) the different radiation dose (our brachytherapy group received 20 Gy, the brachytherapy group studied by Sabate et al, 19 14 Gy).…”
Section: Limitationssupporting
confidence: 65%
“…22 Stent implantation abolishes paradoxical vasoconstriction of coronary stenosis and renders a previous vasoresponsive vessel into a rigid tube. 17 A diminished vasomotor response to exercise has also been reported in patients with hypercholesterolemia, 23 hypertension, or left ventricular hypertrophy. 24 The mechanisms of abnormal coronary vasomotion is different in various disease entities, namely, endothelial dysfunction induced by hypercholesterolemia, media hypertrophy followed by endothelial dysfunction in hypertension, and increased oxygen demand with reduced vasodilatory capacity in patients with LV hypertrophy.…”
Section: Pathophysiological Considerationsmentioning
confidence: 96%
See 1 more Smart Citation
“…Coronary vasomotion has been found to be intact after stent implantation and long-term clinical and angiographic follow-up have attested to the durability of stents. 11,12 Although rare, SAT is associated with a high frequency of major adverse clinical consequences, including markedly increased rates of reinfarction, prolonged hospitalization, and increased costs. The reported incidence of SAT after elective stenting ranges from 0.4 to 3.2%, [13][14][15][16][17] and can be up to 6% in patients with acute coronary syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…Friberg et al (10) estimated that a mean 20% increase of the diameter of the middle cerebral artery using transcranial Doppler and administration of sublingual NTG resulted in a mean 30%% Ϯ 8% increase in the human coronary artery (11). The mean diameter of the MMA in healthy volunteers was 1.4 mm with an SD of 0.18 (pilot study).…”
Section: Sample Size Calculationsmentioning
confidence: 99%